A Robust Molecular Catalyst Generated In Situ for Photo‐ and Electrochemical Water Oxidation. Issue 5 (21st February 2017) - Younus, Hussein A.; Ahmad, Nazir; Chughtai, Adeel H.; Vandichel, Matthias; Busch, Michael; Van Hecke, Kristof; Yusubov, Mekhman; Song, Shaoxian; Verpoort, Francis
Abstract: Water splitting is the key step towards artificial photosystems for solar energy conversion and storage in the form of chemical bonding. The oxidation of water is the bottle‐neck of this process that hampers its practical utility; hence, efficient, robust, and easy to make catalytic systems based on cheap and earth‐abundant materials are of exceptional importance. Herein, an in situ generated cobalt catalyst, [Co II (TCA)2 (H2 O)2 ] (TCA=1‐mesityl‐1, 2, 3‐1 H ‐triazole‐4‐carboxylate), that efficiently conducts photochemical water oxidation under near‐neutral conditions is presented. The catalyst showed high stability under photolytic conditions for more than 3 h of photoirradiation. During electrochemical water oxidation, the catalytic system assembled a catalyst film, which proved not to be cobalt oxide/hydroxide as normally expected, but instead, and for the first time, generated a molecular cobalt complex that incorporated the organic ligand bound to cobalt ions. The catalyst film exhibited a low overpotential for electrocatalytic water oxidation (360 mV) and high oxygen evolution peak current densities of 9 and 2.7 mA cm −2 on glassy carbon and indium‐doped tin oxide electrodes, respectively, at only 1.49 and 1.39 V (versus a normal hydrogen electrode), respectively, under neutral conditions. This finding, exemplified on the in situ generated cobalt complex, might be applicable to other molecular systems and suggests that the formation of a catalytic film in electrochemical water oxidation experiments is not always an indication of catalyst decomposition and the formation of nanoparticles. Abstract : Finding active catalytic species : An in situ generated cobalt catalyst efficiently conducts photo‐ and electrochemical water oxidation under near‐neutral conditions. This work sheds light upon the ability to directly assemble molecular metal–organic catalyst films on the surface of different conducting electrodes for the potential molecular engineering of cobalt‐based electrocatalytic films.